2009
DOI: 10.1039/b900367c
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of hexakis methanofullerene malonate crown-ethers: promising octahedral building blocks for molecular networks

Abstract: Hexaazido and hexaiodo macrocyclic methanofullerenes undergo high-yielding sixfold click reactions or sixfold Heck, Sonogashira and Suzuki cross-coupling reactions, respectively, to yield all organic building blocks for higher molecular architectures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 56 publications
(9 reference statements)
0
34
0
Order By: Relevance
“…Apart from their unique architecture, hexakis adducts derived from the functionalization of the six e double bonds of C 60 are very attractive structures in the synthesis of functional fullerene materials. [45][46][47][48][49][50] The results of the present study lead to the conclusion that the [4+2] cycloaddition of orthoquinodimethanes with the C 60 is a kinetically controlled reaction. The in situ thermal generation of ortho-quinodimethanes from the corresponding 1,2-bis(bromomethyl)benzene precursors requires high temperatures (110 o C) and is followed by the fast, irreversible [4+2] cycloaddition reaction with C 60 to afford thermally stable products.…”
Section: Scheme 6 Synthesis Of Macrocyclic Tether 21mentioning
confidence: 63%
“…Apart from their unique architecture, hexakis adducts derived from the functionalization of the six e double bonds of C 60 are very attractive structures in the synthesis of functional fullerene materials. [45][46][47][48][49][50] The results of the present study lead to the conclusion that the [4+2] cycloaddition of orthoquinodimethanes with the C 60 is a kinetically controlled reaction. The in situ thermal generation of ortho-quinodimethanes from the corresponding 1,2-bis(bromomethyl)benzene precursors requires high temperatures (110 o C) and is followed by the fast, irreversible [4+2] cycloaddition reaction with C 60 to afford thermally stable products.…”
Section: Scheme 6 Synthesis Of Macrocyclic Tether 21mentioning
confidence: 63%
“…The enantiomeric excess was determined by HPLC or GC on chiral stationary phases. General procedure for the sixfold Heck reaction on a fullerene derivative 293 [392]: A mixture of NaHCO 3 (15.0 equiv. ), NBu 4 HSO 4 (6.00 equiv.…”
Section: )mentioning
confidence: 99%
“…Ph Even the extension to a fullerene with six iodophenyl-containing annelated cyclopropanedicarboxylate crown ether-ester units as in 293 is possible, as exemplified by the successful sixfold Heck reaction to give 294 in 94% yield (Scheme 8.62) [392]. Double, triple, and even quadruple Heck-Diels-Alder cascade reactions involving 1,4-diiodo-, 1,3,5-triiodo-, or 1,2,4,5-tetraiodobenzene, respectively, and bicyclopropylidene (16) have been accomplished (cf.…”
mentioning
confidence: 99%
“…In order to overcome this problem, we have recently developed an efficient threestep synthesis of a simple C 60 hexakisadduct derivative bearing 12 azide groups [3] and shown that the copper-mediated Huisgen 1,3-dipolar cycloaddition [4] of azides and alkynes resulting in 1,2,3-triazoles, one of the most powerful click reactions to date, [5] is an ideal tool to efficiently produce functionalized hexasubstituted fullerenes. [3,6,7] In this paper, we now report on the preparation of a C 60 hexakisadduct bearing 12 trimethylsilyl (TMS)-protected alkyne groups allowing the attachment of 12 azide units under the copper-mediated Huisgen 1,3-dipolar cycloaddition conditions. Moreover, by combining these two complementary approaches, we also show that functionalized mixed hexaadducts of C 60 can easily be prepared.…”
mentioning
confidence: 99%